A micromechanically based model for dynamic damage evolution in unidirectional composites. (1st March 2022) - Larsson, R.; Singh, V.; Olsson, R.; Marklund, E.
Abstract: This article addresses the micromechanically motivated, quasistatic to dynamic, failure response of fibre reinforced unidirectional composites at finite deformation. The model draws from computational homogenization, with a subscale represented by matrix and fibre constituents. Undamaged matrix response assumes isotropic viscoelasticity–viscoplasticity, whereas the fibre is transversely isotropic hyperelastic. Major novelties involve damage degradation of the matrix response, due to shear in compression based on a rate dependent damage evolution model, and the large deformation homogenization approach. The homogenized quasi-brittle damage induced failure is described by elastically stored isochoric energy and plastic work of the undamaged polymer, driving the evolution of damage. The developed model is implemented in ABAQUS/Explicit. Finite element validation is carried out for a set of off-axis experimental compression tests in the literature. Considering the unidirectional carbon–epoxy (IM7/8552) composite at different strain rates, it appears that the homogenized damage degraded response can represent the expected ductile failure of the composite at compressive loading with different off-axes. Favourable comparisons are made for the strain and fibre rotation distribution involving localized shear and fibre kinking.